AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN LIDAH MERTUA (Sansevieria trifasciata VAR. LAURENTII) TERHADAP PERTUMBUHAN Klebsiella pneumonia - Siti Fatimah; Yuliana Prasetyaningsih; Naristha Prathi (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2020)
The leaves of the lidah mertua (Sansevieria trifasciata var. Laurentii) contain saponins, alkaloids, flavonoids and polyphenols which work as antibacterials because they can damage bacterial cell walls. This study aims to determine the activity of the ethanol extract of the lidah mertua leaves on the growth of Klebseilla pneumoniae based on the inhibition zone diameter. The test was carried out by extracting the lidah mertua of the in leaves with the maceration method using ethanol as a solvent. This type of research is laboratory experimental. The method used was the inhibition test method with disc discs and tested using a dilution with a concentration of 60%, 70%, 80%, 90%, and 100%. The results showed that the ethanol extract of the in-lidah mertua leaves with a concentration of 60%, 70%, 80%, 90%, and 100% could inhibit the growth of the Klebsiella pneumonia bacteria with an average diameter of the inhibition zone, respectively 7 mm, 10 mm, 11 mm. , 12 mm and 13 mm. The ability to inhibit bacterial growth in the disc disc method for a concentration of 100% is categorized as very strong because it has an average inhibition zone diameter of> 12 mm, for a concentration of 70%, 80%, and 90% is categorized as strong because it has an average inhibition zone diameter of 8- 12 mm, while the 60% concentration is categorized as weak because it has an average inhibition zone diameter of <8 mm based on the Vasanthakumari category. The antibacterial activity test in inhibiting the growth of Klebsiella pneumonia has the highest value at a concentration of 100%